Association between Prolactin Receptor (PRLR) gene polymorphisms and litter size in Katjang-Boer hybrid goats - Mohd Nadzir, Mohd Noor Hisham; M. S. Suhaimi, Ainu Husna; M. O., Nurulhuda; A., Noor Athirah; O., Mohd Firdaus; J. L., Poh (Malaysian Society of Animal Production, 2024)
Goat fertility is essential for farm productivity and economic viability. This study investigates the association between Prolactin Receptor (PRLR) gene polymorphism and litter size in Katjang-Boer hybrid goats. DNA from 43 goats was analyzed using five primers targeting different regions of the PRLR gene. Polymerase chain reaction (PCR) and Single-Strand Conformation Polymorphism (SSCP) were employed to detect genetic variation. The association between litter size, breeding year, and PRLR polymorphism was determined using Kruskal-Wallis and Mann-Whitney U tests. Results indicate a significant association between PRLR gene polymorphisms in intron 1 and intron 2 with litter size (p < 0.05). Specifically, the AH genotype in intron 1 was significantly associated with larger litter sizes (1.58 ± 0.19, p < 0.05). No significant associations were found for exon 9 and 3’UTR regions. Breeding year also significantly influenced litter size, with the highest numbers observed in the later parity. These findings provide insights for improving farm productivity through genetic selection.